Pathogenesis and Classification of Chiari Malformation Type I Based on the Mechanism of Ptosis of the Brain Stem and Cerebellum: A Morphometric Study of the Posterior Cranial Fossa and Craniovertebral Junction - Nishikawa, Misao; Bolognese, Paolo A.; Kula, Roger W.; Ikuno, Hiromichi; Ohata, Kenji (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction We investigated the mechanism of ptosis of the brain stem and cerebellum (hindbrain) in Chiari malformation type I (CM-I) and classified CM-I according to pathogenesis, based on a morphometric study of the posterior cranial fossa (PCF) and craniovertebral junction (CVJ). We discuss the appropriate surgical treatment for hindbrain ptosis.Materials and Methods We examined 500 patients with CM-I and 100 healthy control individuals. We calculated the volume of the PCF (VPCF) and measured the axial length of the enchondral parts of the occipital bone and hindbrain. As statistical analyses, for the multiple analyses, heavy palindromic tests were used. Using three independent objective parameters, we tried to classify CM-I.Results Three independent subtypes were confirmed (CM-I types A, B, and C). CM-I type A (167 cases): normal VPCF, normal volume of the area surrounding the foramen magnum (VSFM), and normal occipital bone size; CM-I type B (178 cases): normal VPCF, small VSFM, and small occipital bone size; and CM-I type C (155 cases): small VPCF, small VSFM, and small occipital bone size.Conclusions Morphometric analyses of PCF and CVJ were very useful for the investigation of the mechanism of hindbrain ptosis and classifying CM-I according to pathogenesis. CM-I type A included mechanisms other than hindbrain ptosis, for example, CVJ instability, tethered cord, and increased intracranial pressure. CM-I types B and C demonstrated underdevelopment of the occipital bone. For CM-I types B and C, posterior decompression should be performed. For CM-I type A, appropriate surgical management should be selected.
Keywords: Chiari malformation; morphometric study; posterior cranial fossa; craniovertebral junction; surgical management